(untitled) (Nigerian Journal of Technology, 2016)
Nigeria automobile service industry is labour intensive with high level of work-related injuries among its workforce. This research assessed work-space (WsD) and work-method designs (WmD), level of compliance with recommended standards (RSs) and effects on workers’ wellbeing. Clearances for services in 55 supine positions and 45 stand-up workbenches’ (SUWb) heights were measured and compared with RSs. Questionnaires were completed among 252 workers to measure prevalence of work-related injuries. Descriptive statistical procedure and Chi-Square tests were conducted using SPSS. 94.4% of workers suffered from low back, 43.5% neck and 40% knees pains among others. Averagely, 43.33±7.3cm and 67±0.15cm were measured for supine position clearance and SUWb heights with 15.03±14.3 and 26.55±16.23 percentage deviations respectively from the minimum RSs. Automotive mechanics may be prone to back, hand and/or wrist related problems and Cumulative Trauma Disorders. Ergonomics trainings, use of mechanical devices and protective equipment will reduce injuries connected with the job. http://dx.doi.org/10.4314/njt.v35i2.12